Mastering Lync Server 2010. - Winters, Nathan (John Wiley & Sons, 2012)
An in-depth guide on the leading Unified Communications platformMicrosoft Lync Server 2010 maximizes communication capabilities in the workplace like no other Unified Communications (UC) solution. Written by experts who know Lync Server inside and out, this comprehensive guide shows you step by step how to administer the newest and most robust version of Lync Server. Along with clear and detailed instructions, learning is aided by exercise problems and real-world examples of established Lync Server environments. You'll gain the skills you need to effectively deploy Lync Server 2010 and be on y.